The Power Muth Distribution∗ - Pedro Jodra; Hector Wladimir Gomez; Maria Dolores Jimenez-Gamero; Maria Virtudes Alba-Fernandez (Mathematical Modelling and Analysis, 2017)
Muth introduced a probability distribution with application in reliability theory. We propose a new model from the Muth law. This paper studies its statistical properties, such as the computation of the moments, computer generation of pseudo-random data and the behavior of the failure rate function, among others. The estimation of parameters is carried out by the method of maximum likelihood and a Monte Carlo simulation study assesses the performance of this method. The practical usefulness of the new model is illustrated by means of two real data sets, showing that it may provide a better fit than other probability distributions.